Adaptive Hysteresis-Band Current Controller of a Three Phase Induction Machine - A. Mahir, Rami; J. H. , Amjad; Q. Hussien, Ayad (Journal of Engineering and Sustainable Development, 2010)
Hysteresis current control is one of the simplest techniques used to control the magnitude and phase angle of three-phase motor currents for high-speed drive systems. It is well-known for its simplicity of implementation and inherent peak current limiting capability. However, conventional fixed-band hysteresis control has a variable switching frequency throughout the fundamental period, and consequently, the load current harmonic ripple is not optimal. In this paper, an adaptive hysteresis band current controller (HBCC) is described and its performance and effectiveness are checked in case of the presence and absence of the speed loop of an indirect field-oriented controlled induction machine (IFOC IM).